Impact of anthropogenic landscape alteration on the distribution of potential cheetah (Acinonyx jubatus) habitats in southern Kenya: Revealing cheetah behavioural change - Noreen M. Mutoro; Jonas Eberle; Mary Wykstra; Jan Christian Habel; Gertrud Schaab (Global Ecology and Conservation, 2025)
The current resident cheetah (Acinonyx jubatus) distribution range is predominantly outside protected areas where anthropogenic pressures are rapidly changing the composition and structure of the landscape. Yet, little is known about the effects of infrastructure development, human/ livestock population growth and land use/cover change on cheetah habitat distribution in these landscapes. This study investigated changes in the distribution of potential cheetah habitats following major human disturbance in a resident cheetah range outside a protected area in southern Kenya. MaxEnt-based distribution models were built using past (2005–2011) and current (2012–2019) cheetah occurrence records together with a combination of 16 environmental, anthropogenic and biotic covariates. The results show that potential cheetah habitats were widely distributed, with habitat suitability mainly influenced by precipitation of the driest season, slope, and distribution of potential prey habitats. Habitats declined by almost 50 % following major disturbance, with highly suitable cheetah habitats shifting to the western part of the study area. Some habitats became fragmented and much smaller in size and the distribution of potential prey habitats, temperature seasonality-annual range and elevation mostly influenced habitat suitability. By projecting the past species-environment relationship onto current predictors and comparing the results with the geographic distribution derived from the current cheetah observation data, changes in cheetah behaviour were revealed. Anthropogenic activities are causing habitat fragmentation, loss and shifts in ecological niches, triggering behavioural change with cheetahs avoiding unsuitable habitats. As human disturbance increases, we recommend regular and targeted monitoring of cheetahs in remaining suitable habitats to assess threats to cheetah survival.